The effects of sleep and targeted memory reactivation on the consolidation of relevant and irrelevant information - Barner, Christine; Werner, Ann-Sophie; Schörk, Sandra; Born, Jan; Diekelmann, Susanne (Frontiers in Sleep, 2023)
Introduction Sleep is assumed to facilitate the consolidation of new memories in an active process of covert reactivation of the underlying memory representations. Recent evidence suggests that this process is selective by favoring memories that are of future relevance, and can be externally triggered by learning-associated sensory cues presented during sleep [i.e., targeted memory reactivation (TMR)]. In the present study, we (1) set out to confirm the preferential sleep effect for relevant information, and then asked whether (2) simultaneous TMR of relevant and irrelevant information facilitates the advantage for relevant information, and (3) whether the preferential benefit of sleep and TMR for relevant information persists over time. Methods To test these questions, participants explicitly learned two sets of picture-location associations, of which one set was instructed (after encoding) to be relevant and the other to be irrelevant for later testing. In Experiment 1, memory was tested after ~12 h of night sleep (n = 28) or daytime wakefulness (n = 28) as well as again after ~1 week. Results Results showed overall better memory retention after sleep compared to wakefulness after 12 h as well as after 1 week. The relevant memories were overall retained better than the irrelevant memories. Interestingly, a trend toward a stronger sleep benefit for the relevant memories emerged after 1 week, although this effect failed to reach significance. In Experiment 2, learning of the relevant and irrelevant picture-location associations took place in the presence of an odor. During subsequent sleep, in the first phase of slow wave sleep (SWS), participants were either presented with the odor again (n = 23) or received an odorless vehicle (n = 20). Memory retention was assessed after the first SWS period (following awakening) as well as after ~one week. As in Experiment 1, relevant memories were overall retained better than irrelevant memories. However, TMR did not differentially affect the retention of relevant and irrelevant memories. Discussion These findings provide tentative evidence that the selective benefit of sleep for relevant memories evolves over time but is not further facilitated by TMR.